It is currently 19 Sep 2017, 13:57

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Why does square root of (x^2-6x+9) = 3-X???

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

### Hide Tags

Intern
Joined: 18 Oct 2013
Posts: 12

Kudos [?]: [0], given: 1

Why does square root of (x^2-6x+9) = 3-X??? [#permalink]

### Show Tags

10 Nov 2013, 10:06
Just as the title, stated above, why does the square root of (x^2-6x+9) = 3-x???? Shouldn't it equal x-3??? Thank you.

Kudos [?]: [0], given: 1

Director
Affiliations: GMATQuantum
Joined: 19 Apr 2009
Posts: 603

Kudos [?]: 480 [0], given: 17

Re: Why does square root of (x^2-6x+9) = 3-X??? [#permalink]

### Show Tags

10 Nov 2013, 20:57
The outcome of sqrt(x^2-6x+9) depends on the value of x. If x >= 3, then sqrt(x^2-6x+9)=x-3, however if x<3, then sqrt(x^2-6x+9)=3-x. For example, if x=4, then sqrt(x^2-6x+9)=sqrt(16-24+9)=sqrt(1)=1, which is indeed equal to x-3=4-3=1. However, if x=0, then sqrt(x^2-6x+9)=sqrt(0-0+9)=sqrt(9)=3, which is indeed equal to 3-x=3-0=3.

The reason for this simplification is based on the identity sqrt(x^2)=|x|. In this particular case sqrt(x^2-6x+9) = sqrt[(x-3)^2]=|x-3| and the absolute value expression can be rewritten based on the value of x, if x>=3, then |x-3|=x-3, and if x<3, then |x-3|=3-x.

In summary, sqrt(x^2-6x+9) = x-3 if x>=3 and sqrt(x^2-6x+9) = 3-x if x<3. In the question you encountered, it was probably a data sufficiency question where they added the constraint x<3.

Kudos [?]: 480 [0], given: 17

Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 7604

Kudos [?]: 16875 [0], given: 230

Location: Pune, India
Re: Why does square root of (x^2-6x+9) = 3-X??? [#permalink]

### Show Tags

12 Nov 2013, 23:38
carpediem437 wrote:
Just as the title, stated above, why does the square root of (x^2-6x+9) = 3-x???? Shouldn't it equal x-3??? Thank you.

$$(x^2-6x+9) = (x - 3)^2$$

Note that:
$$\sqrt{y^2} = |y|$$ (it is not y, it is mod y)
$$\sqrt{(x - 3)^2} = |x - 3|$$

Now |x - 3| can be (x - 3) or (3 - x). It depends on the value of x.

Now note how you handle mods:
|y| = y if y > 0
|y| = -y is y < 0

So, |x - 3| = x - 3
if (x - 3) >= 0 i.e. x >= 3

|x - 3| = -(x - 3) = 3 - x
If (x - 3) < 0 i.e. x < 3

So, the value of $$\sqrt{(x^2-6x+9)}$$ depends in the value of x. It is (x - 3) if x >= 3 and it is (3 - x) if x < 3.
_________________

Karishma
Veritas Prep | GMAT Instructor
My Blog

Get started with Veritas Prep GMAT On Demand for \$199

Veritas Prep Reviews

Kudos [?]: 16875 [0], given: 230

Re: Why does square root of (x^2-6x+9) = 3-X???   [#permalink] 12 Nov 2013, 23:38
Similar topics Replies Last post
Similar
Topics:
Square of a exponent with root 1 17 Jul 2010, 21:33
31 Dec 1969, 17:00
Inequality and Squares under square root 1 02 May 2017, 09:28
1 What is Square root of x squared 2 08 Oct 2014, 07:54
1 SQUARE ROOTS 10 20 Apr 2017, 01:16
Display posts from previous: Sort by

# Why does square root of (x^2-6x+9) = 3-X???

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.